Protocol for the development and validation of risk prediction equations to estimate absolute and conditional survival in patients with cancer - Hippisley-Cox, Julia; Coupland, Carol (University of Nottingham, 2016)
This is a protocol to describe the development and validation of a set of prediction equations to quantify absolute survival for patients with different types of cancers taking account of other clinical factors available through routine linkage of cancer registry data to primary care electronic health records. We will also include estimates of conditional survival since it may be a more accurate measure of survival among those surviving the first year, especially when the initial prognosis is poor, such as with advanced stage colorectal cancer. Such estimates can be used to provide better information for patients and doctors to help inform treatment and other life decisions.